1999
DOI: 10.1002/hep.510290336
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of 1762T 1764A Mutations in the Basic Core Promoter of Hepatitis B Virus Isolated From Black Africans With Hepatocellular Carcinoma Compared With Asymptomatic Carriers

Abstract: The purpose of this study was to identify mutations in the basic core promoter and enhancer II region of the hepatitis B virus (HBV) that might cause the HBV e antigen (HBeAg)-negative phenotype and contribute to hepatocarcinogenesis in black African carriers of the virus. The basic core promoter/enhancer II overlaps with the X gene. HBV DNA from serum of 47 asymptomatic carriers and 50 patients with hepatocellular carcinoma and from 28 tumor and 10 nontumor liver tissues was amplified and sequenced directly. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
219
7

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 244 publications
(245 citation statements)
references
References 53 publications
19
219
7
Order By: Relevance
“…13,18,25,26,36 Furthermore, hepatocellular carcinoma has been reported in association with BCP mutations. 26,37 Although the mechanism underlying the occurrence of BCP mutations is unclear, the patients with age greater than or equal to 35 years were at an increased risk for having them ( Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…13,18,25,26,36 Furthermore, hepatocellular carcinoma has been reported in association with BCP mutations. 26,37 Although the mechanism underlying the occurrence of BCP mutations is unclear, the patients with age greater than or equal to 35 years were at an increased risk for having them ( Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Although HBx expression is often detected in HBV-related HCCs (Feitelson and Duan, 1997), the prognosis and/or prevalence of metastasis of HBx-expressing tumors has not been studied so far. In addition, it has been shown that the X gene is often mutated in HCCs Baptista et al, 1999;Poussin et al, 1999). However, these mutations accumulate preferently within the transactivation domains of HBx, without a ecting HBx-mediated cell transformation (Gottlob et al, 1998b).…”
Section: Discussionmentioning
confidence: 99%
“…The HBV genome encodes its essential genes with overlapping ORFs; therefore, a mutation in the HBV genome can alter the expression of multiple proteins. In many cases of HCC in China and Africa, a double mutation in the HBV genome, an adenine-to-thymine transversion at nucleotide 1762 and a guanine-to-adenine transition at nucleotide 1764 (1762 T ͞ 1764 A ), has been found in tumors (5,10,11). This segment of the HBV genome contains an overlapping sequence for the base core promoter and the HBV X gene; therefore, the double mutation in codons 130 and 131 of the HBV X gene reported in human HCC is identical to the 1762 and 1764 nucleotide changes (12,13).…”
mentioning
confidence: 99%
“…This segment of the HBV genome contains an overlapping sequence for the base core promoter and the HBV X gene; therefore, the double mutation in codons 130 and 131 of the HBV X gene reported in human HCC is identical to the 1762 and 1764 nucleotide changes (12,13). The onset of these mutations has been also associated with the increasing severity of the HBV infection and cirrhosis (10,11). Thus, the tracking of this polymorphism with disease outcomes makes it a candidate biomarker for early detection of HCC risk in individuals.…”
mentioning
confidence: 99%